Maro Pengolahan Sawah Dalam Perspektif Hukum Ekonomi Islam - Aula Izatul Aini; Komarudin A; Muhammad Imam Khaudli; Devi Wahyuningtyas (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This research aims to find out how the practice of collaborating with rice processing in the Tamanagung Village, Cluring District, Banyuwangi, and knowing how to practice the cooperation with processing of maro in The Tamanagung Village, Cluring District, Banyuwangi the perspective of Islamic economic law. The type used in this study is descriptive analysis, which describes the data that researchers collect both from observations, interviews and documentation. Data analysis uses interactive model analysis techniques. The results of the study are the collaboration carried out by the owner of the paddy field and the paddy farmer, the paddy owner only provides land only, while the paddy cultivator is burdened with material capital and labor to work on the paddy. The practice of maro processing in paddy fields in Tamanagung Village, Cluring District, Banyuwangi Regency is included in the mukhabarah contract. The profit sharing mechanism uses the bawon system (crop maintenance fee). If 100% of the yield is obtained, 20% will be given to the cultivators of the paddy fields, while the remaining 80% of the deduction will be collected between the two parties where each party will get an equal 40% yield.